2023
DOI: 10.1093/pnasnexus/pgad012
|View full text |Cite
|
Sign up to set email alerts
|

Local calcium signal transmission in mycelial network exhibits decentralized stress responses

Abstract: Many fungi live as mycelia, which are networks of hyphae. Mycelial networks are suited for the widespread distribution of nutrients and water. The logistical capabilities are critical for the extension of fungal survival areas, nutrient cycling in ecosystems, mycorrhizal symbioses, and virulence. In addition, signal transduction in mycelial networks is predicted to be vital for mycelial function and robustness. A lot of cell biological studies have elucidated protein and membrane trafficking and signal transdu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…Furthermore, the migration decision of P. velutina mycelium was affected by the waiting time for the bait, i.e., the quality change of the original inoculum wood (Fukasawa and Kaga, 2021). If mycelium, as a modular organism, responds locally to these environmental stimuli (Itani et al, 2023), the NEAR experiment in the present study may have resulted in two separate parts of the mycelium responding to the bait, more or less, independently: the small part of the mycelium close to the original inoculum, and the larger spreading fans, including the growing front. Given that most of the nutrients are likely directed toward the growing front, the small part of the mycelium must respond to the new bait without a sufficient allocation of nutrients, which likely induces migration.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the migration decision of P. velutina mycelium was affected by the waiting time for the bait, i.e., the quality change of the original inoculum wood (Fukasawa and Kaga, 2021). If mycelium, as a modular organism, responds locally to these environmental stimuli (Itani et al, 2023), the NEAR experiment in the present study may have resulted in two separate parts of the mycelium responding to the bait, more or less, independently: the small part of the mycelium close to the original inoculum, and the larger spreading fans, including the growing front. Given that most of the nutrients are likely directed toward the growing front, the small part of the mycelium must respond to the new bait without a sufficient allocation of nutrients, which likely induces migration.…”
Section: Resultsmentioning
confidence: 99%
“…[85] R-GECO, based on a red fluorescent protein (RFP) characterized by a red-shifted emission, enables deep-tissue imaging and has been employed to investigate wavy propagation and blinking calcium signals in externally stimulated Aspergillus nidulans. [86] GCaMP probes, typically sourced from the fusion of calmodulin, M13 peptide, and green fluorescent protein (GFP), emit green fluorescence upon binding to calcium ions. [87] Live-cell imaging of fungal cells shows Ca 2+ -specific responses in Candida albicans exposed to membrane, osmotic, and oxidative stressors [88] and Saccharomyces cerevisiae in response to pheromones.…”
Section: Recording Fungal Signalsmentioning
confidence: 99%
“…Similarly, Fukasawa et al 25 reported that the fruit bodies of an ectomycorrhizal fungus Laccaria bicolor exhibited electrical potential following a rainfall event, with causal relationships observed in their patterns across the neighboring fruit bodies. Nonetheless, this transfer of electrical signals across the entirety of the mycelia remains a subject of debate and ongoing research 26 .…”
Section: Introductionmentioning
confidence: 99%